A new insight: crosstalk between neutrophil extracellular traps and the gut-liver axis for nonalcoholic fatty liver disease - Jinping Yin; Jinping Yin; Yanli Zhu; Rongrong Liu; Weixin Wang; Zhicheng Wang; Jianfeng Wang (Frontiers in Immunology, 2025)
Non-alcoholic fatty liver disease (NAFLD) is a widespread chronic liver disorder, affecting nearly a quarter of the global population. It progresses from simple steatosis to non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and hepatocellular carcinoma (HCC). The gut-liver axis is crucial in NAFLD progression, driven by intestinal barrier dysfunction, microbial translocation, and immune dysregulation. Neutrophil extracellular traps (NETs)—web-like structures of DNA, histones, and inflammatory proteins—promote chronic inflammation and liver injury. This review examines the role of NETs in gut-liver axis crosstalk and NAFLD progression. It explores how NETs amplify inflammation, contribute to fibrosis, and facilitate the progression from NAFLD to HCC by interacting with gut microbiota and immune signaling pathways. Therapeutic strategies targeting NETs, such as reducing their formation, enhancing degradation, and modulating the gut microbiota, offer promising approaches to mitigate disease progression. This review sheds light on the interplay between NETs and the gut-liver axis, offering new insights into NAFLD pathophysiology and potential therapeutic strategies to improve patient outcomes.